2017
DOI: 10.31235/osf.io/8e4sa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solidarity or Schism: Ideological Congruence and the Twitter Networks of Egyptian Activists

Abstract: Social movements scholarship on the role of coalitions in advancing social change claims that communication across ideological boundaries can foster a collective identity among diverse groups of activists. New communications technology, especially activists' widespread adoption of social media, calls into question whether these claims apply equally to online social media-based coalitions. Using the case of the Egyptian revolution in the Arab Spring, we conduct a series of social network analyses of the Twitter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Twitter and other social media platforms offer advocacy groups a lowcost means to swiftly disseminate information, build relationships, and mobilize supporters [31,42]. Twitter, in particular, has become an established platform for activists to raise awareness and mobilize about various issues ranging from environmentalism [64] to protests during the Arab Spring period [2].…”
Section: Expected Stakeholders On Twittermentioning
confidence: 99%
“…Twitter and other social media platforms offer advocacy groups a lowcost means to swiftly disseminate information, build relationships, and mobilize supporters [31,42]. Twitter, in particular, has become an established platform for activists to raise awareness and mobilize about various issues ranging from environmentalism [64] to protests during the Arab Spring period [2].…”
Section: Expected Stakeholders On Twittermentioning
confidence: 99%
“…The literature questioning the relationship between the online and offline dimension of collective action is rapidly expanding [38,47,69], still the debate remains open between two competing camps: while some consider that social media generates novel forms of political participation and organization [39,4], others contend that digital activism has a limited reach, as aggrieved populations do not have access to (or do not confine their grievances) connected devices [59,50]. In addition, other scholars highlight the fragility of the "social media effect" over time [1]. Nevertheless, scholars have found that social media activity has acquired growing importance in contentious politics [70,48].…”
Section: State Of the Art: Social Media And Onsite Protestsmentioning
confidence: 99%
“…Since the introduction of the Internet, SMOs and activists have found ICTs useful for planning and staging protest events, both online and offline. Studies of well‐known recent and current social movements, including Occupy, Arab Spring, and the Movement for Black Lives, show the importance of ICTs to the emergence of these movements (e.g., Abul‐Fottouh and Fetner ; Gamson and Sifry ; Nielsen ; Ray et al. ; Tufekci ).…”
Section: Movements Organizations and Individuals In The Digital Agementioning
confidence: 99%